A weighted full-Newton step primal-dual interior point algorithm for convex quadratic optimization - Mohamed, Achache (Statistics, optimization & information computing, 2014)
In this paper a new weighted short-step primal-dual interior point algorithm to solve convex quadratic optimization (CQO) problems. The algorithm uses at each interior iteration afull-Newton step and the strategy of the central to obtain an epsilon-optimal solution of CQO. The algorithm yields the best currently best known theoretical complexity bound namely O(\sqrt(n) log n/epsilon).